Capillary bacterial migration on non-nutritive solid surfaces - Ivanković Tomislav; Hadad Uzi; Kushmaro Ariel; Dekić Svjetlana; Ćevid Josipa; Percela Marko; Hrenović Jasna (Arhiv za Higijenu Rada i Toksikologiju, 2020)
Here we describe an additional type of bacterial migration in which bacterial cells migrate vertically across a non-nutritive solid surface carried by capillary forces. Unlike standard motility experiments, these were run on a glass slide inserted into a Falcon tube, partly immersed in a nutrient medium and partly exposed to air. Observations revealed that capillary forces initiated upward cell migration when biofilm was formed at the border between liquid and air. The movement was facilitated by the production of extracellular polymeric substances (EPS). This motility differs from earlier described swarming, twitching, gliding, sliding, or surfing, although these types of movements are not excluded. We therefore propose to call it “capillary movement of biofilm”. This phenomenon may be an ecologically important mode of bacterial motility on solid surfaces.